Dynamic power saving for CMOS circuits - Yeap, Kim Ho; Ng, Len Luet; Ahmad Uzair Mazlan; Loh, Siu Hong; Tshai, Kim Hoe (Penerbit Universiti Kebangsaan Malaysia, 2024)
With more functionalities being integrated into a microchip today, higher processing power is drawn. As a result of this, clock and logic power consumption has turned out to be a critical issue to be coped with by chip designers. In this paper, we present various power-saving approaches employed in complementary metal oxide semiconductor (CMOS) circuit designs. The approaches involve restructuring the logic circuits, performing clock gating, and selecting the appropriate circuits for counters and frequency divisions. In order to show their efficacies in power optimization, the approaches were applied to a phase-locked loop (PLL), clock divider (CD), full adder (FA), counter, arithmetic logic unit (ALU), and microprocessor without interlocked pipelined stages (MIPS) circuits and validated using Intel Quartus Prime Lite and Mentor Graphics Modelsim. The following conclusions can be drawn from the results: Firstly, the efficacy of minimizing power dissipation using logic restructuring is found to be in direct proportion with the rate of the switching activity (SA); secondly, a maximum of 3.5% of thermal power dissipation can be saved using clock gating; thirdly, gray counters give the lowest power consumption; and, finally, the thermal power estimation for the phase-locked loop (PLL) is relatively higher than that for the clock divider (CD) when both of them are implemented for dividing frequencies.